ARA290, a Specific Agonist of Erythropoietin/CD131 Heteroreceptor, Improves Circulating Endothelial Progenitors' Angiogenic Potential and Homing Ability. Issue 4 (October 2016) - Hache, Guillaume; Garrigue, Philippe; Bennis, Youssef; Stalin, Jimmy; Moyon, Anais; Cerami, Anthony; Brines, Michael; Blot-Chabaud, Marcel; Sabatier, Florence; Dignat-George, Francoise; Guillet, Benjamin
ABSTRACT: Background: Alternate erythropoietin (EPO)-mediated signaling via the EPOR/CD131 heteromeric receptor exerts the tissue-protective actions of EPO in a wide spectrum of injuries, especially ischemic diseases. Circulating endothelial progenitor cells contribute to endothelial repair and post-natal angiogenesis after chronic ischemic injury. This work aims to investigate the effects of ARA290, a specific agonist of EPOR/CD131 complex, on a subpopulation of endothelial progenitor cells named endothelial colony-forming cells (ECFCs) and to characterize its contribution to ECFCs-induced angiogenesis after peripheral ischemia. Methods: ARA290 effects on ECFCs properties were studied using cell cultures in vitro . We injected ARA290 to mice undergoing chronic hindlimb ischemia (CLI) in combination with ECFC transplantation. The homing of transplanted ECFC to ischemic tissue in vivo was assessed by SPECT/CT imaging. Results: In vitro, ARA290 enhanced the proliferation, migration, and resistance to H2 O2 -induced apoptosis of ECFCs. After ECFC transplantation to mice with CLI, a single ARA290 injection enhanced the ischemic/non-ischemic ratio of hindlimb blood flow and capillary density after 28 days and the homing of radiolabeled transplanted cells to the ischemic leg 4 h after transplantation. Prior neutralization of platelet-endothelial cell adhesion molecule-1 (CD31) expressed by the transplanted cells inhibited ARA290-induced improvement of homing. Discussion: ARA290 induces specific improvement of the biological activity of ECFCs. ARA290 administration in combination with ECFCs has a synergistic effect on post-ischemic angiogenesis in vivo . This potentiation appears to rely, at least in part, on a CD31-dependent increase in homing of the transplanted cells to the ischemic tissue.